ANALISIS PERSEPSI PEKERJA MEDIA PENYIARAN DI SURABAYA TERHADAP PEMANFAATAN AI VIDEO GENERATOR DI CHANNEL YOUTUBE @TVONE.AI - Bulan Rachmadhany, Agnie; Arviani, Heidy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advances in Artificial Intelligence (AI) in the broadcasting industry have spurred various innovations in the news production process, one of which is the use of video generators. This technology enables the creation of news content featuring virtual presenters, which can improve production efficiency and accelerate the distribution of information. One media outlet in Indonesia that has implemented this innovation is the YouTube channel @tvOne.ai. Although it offers various benefits, the use of video generators has also sparked diverse perspectives regarding journalistic quality, the ethics of AI use, and the future of media professionals. This study aims to understand how broadcast media workers in Surabaya perceive the use of video generators on the YouTube channel @tvOne.ai. This study employs a descriptive qualitative approach. Data were collected through in-depth interviews with six informants who work as broadcast media professionals in Surabaya. The results show that media professionals view video generators as an innovation that can support the efficiency of news production; however, they are not yet capable of fully replacing the human role because they still require supervision, verification, and ethical considerations in journalistic practice. Differences in perception are also influenced by the experience, knowledge, and roles of each informant in the news production process.